International outsourcing and trade union (de-)centralisation - Lommerud, Kjell Erik (2019)
We study the effects of centralised versus decentralised wage setting in a unionsed duopoly where firms can outsource parts of input production to foreign subcontractors. We show that decentralised (as opposed to centralised) wage setting allows trade unions to capture a larger share of the rents generated by international outsourcing. Consequently, the equilibrium degree of outsourcing is lower under decentralised wage setting, which benefits unions if they are sufficiently employment oriented. We identify situations in which both firms and unions prefer decentralised over centralised wage setting. Thus, international outsourcing opportunities is a potential driver of trade union decentralisation.